KEJADIAN KUSTA DI ACEH BARAT, INDONESIA: STUDI TENTANG FAKTOR RISIKO - Rawanita, Misdar; Indah, Rosaria; Fahdhienie, Farrah; Diana, Mutia (Jurnal Manajemen Kesehatan Indonesia, 2025)
Leprosy is an infectious disease caused by Mycobacterium leprae that primarily affects the peripheral nerves, skin, and other body tissues. This study aimed to examine the association between various risk factors and the incidence of leprosy. A case-control design was employed, comprising a case group of 15 multibacillary leprosy patients and a control group of 45 household members without leprosy. Data analysis included univariate and bivariate analyses, with the latter performed using the chi-square test. The findings revealed significant associations between leprosy incidence and several risk factors: age (P = 0.004, OR = 13.391; CI = 1.621–110.596), lack of knowledge (P = 0.042, OR = 4.75; CI = 0.957–23.572), duration of contact (P = 0.007, OR = 0.182; CI = 0.049–0.668), close contact (P = 0.007, OR = 0.182; CI = 0.049–0.668), and socioeconomic status (P = 0.021, OR = 5.688; CI = 1.149–28.163). These results highlight the necessity of enhancing educational and counseling initiatives for at-risk populations, particularly those residing near leprosy patients, while also encouraging individuals affected by leprosy to complete their treatment regimen.